2016
DOI: 10.14778/3007263.3007271
|View full text |Cite
|
Sign up to set email alerts
|

Database system support of simulation data

Abstract: Supported by increasingly efficient HPC infrastructure , numerical simulations are rapidly expanding to fields such as oil and gas, medicine and meteorology. As simulations become more precise and cover longer periods of time, they may produce files with terabytes of data that need to be efficiently analyzed. In this paper, we investigate techniques for managing such data using an array DBMS. We take advantage of multidimensional arrays that nicely models the dimensions and variables used in numerical simulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Since SciDB splits the array into chunks, which are equally sized subarrays, it becomes necessary to define a balanced partitioning scheme when dealing with irregularly distributed data. For sparse arrays, this is seldom a trivial task, since a poor partitioning scheme may impact query response time, greatly affecting database performance [Lustosa et al 2016]. Rasdaman [Baumann et al 1998] was a pioneer array DBMS that estabilished arrays as first-class database structures.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…Since SciDB splits the array into chunks, which are equally sized subarrays, it becomes necessary to define a balanced partitioning scheme when dealing with irregularly distributed data. For sparse arrays, this is seldom a trivial task, since a poor partitioning scheme may impact query response time, greatly affecting database performance [Lustosa et al 2016]. Rasdaman [Baumann et al 1998] was a pioneer array DBMS that estabilished arrays as first-class database structures.…”
Section: Related Workmentioning
confidence: 99%
“…A few Array data processing systems have appeared recently offering a data model and query algebra adequate for representing and processing non-Relational data [Baumann et al 1998, Stonebraker et al 2011, Lustosa et al 2016, Zalipynis 2018]. In particular, SciDB was conceived having large scale scientific data management as target applications [Brown 2010], such as data produced by the Sloan Digital Sky Survey.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous study on the usage of DBMSs to manage numerical simulation data [Lustosa et al 2016] highlighted many difficulties regarding scientific array data representation. We concluded that the idiosyncrasies of this kind of data are not well represented by current array data models.…”
Section: Introductionmentioning
confidence: 99%
“…For each time step previously defined, the mesh is updated with new values for its vertices and edges. A native representation for this kind of data are multidimensional matrices [Lustosa et al 2016].…”
Section: Introductionmentioning
confidence: 99%